Menopausal hormonal therapy or non-hormonal treatment: rational choice - T Yu Pestrikova; E A Yurasova; T V Yachinskaya; T D Kovalyova (IP Berlin A.V., 2015)
Patients with the "climacteric syndrome" diagnosis make only 1,0% in structure of the general incidence of the women who visit the female consultation, and 1.6% - total of the patients consisting on the dispensary account. The patients who are health workers ask for medical care less than managers, teachers. Patients with the diagnosis of a climacteric syndrome had a certain relation to reception of the menopausal hormonal therapy (MHT). So, 22.69% of patients initially feel fear of reception of hormonal preparations; 16.81% - pass to reception of MHT after absence of effect from reception of non-hormonal therapy. Only 16.81% of patients have contraindications to reception of MHT.Purpose of MHT (a combination of estradiol to 1 mg / drospirenone 2 mg) renders high medical effect at patients with a climacteric syndrome (p